2010
DOI: 10.2134/jeq2009.0240
|View full text |Cite
|
Sign up to set email alerts
|

Coarse Particulate Matter Emissions from Cattle Feedlots in Australia

Abstract: Open cattle feedlots are a source of air pollutants that include particular matter (PM). Over 24 h, exposure to ambient concentrations of 50 microg m(-3) of the coarse-sized fraction PM (aerodynamic diameter <10 microm [PM(10)]) is recognized as a health concern for humans. The objective of our study was to document PM(10) concentration and emissions at two cattle feedlots in Australia over several days in summer. Two automated samplers were used to monitor the background and in-feedlot PM(10) concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
3
20
1
Order By: Relevance
“…During the 17‐mo measurement period, hourly PM 10 flux ranged from ~0 to 272 mg m −2 h −1 , with an overall median value of 36 mg m −2 h −1 . Based on days with at least 12 hourly fluxes ( n = 44), the overall median daily PM 10 flux was 1.81 g m −2 d −1 , which was slightly higher but within range of those recently published for beef cattle feedlots (McGinn et al, 2010; Bonifacio et al, 2012). McGinn et al (2010) reported values of 1.45 and 1.61 g m −2 d −1 for Australian feedlots based on inverse dispersion modeling with WindTrax.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…During the 17‐mo measurement period, hourly PM 10 flux ranged from ~0 to 272 mg m −2 h −1 , with an overall median value of 36 mg m −2 h −1 . Based on days with at least 12 hourly fluxes ( n = 44), the overall median daily PM 10 flux was 1.81 g m −2 d −1 , which was slightly higher but within range of those recently published for beef cattle feedlots (McGinn et al, 2010; Bonifacio et al, 2012). McGinn et al (2010) reported values of 1.45 and 1.61 g m −2 d −1 for Australian feedlots based on inverse dispersion modeling with WindTrax.…”
Section: Resultssupporting
confidence: 79%
“…Based on days with at least 12 hourly fluxes ( n = 44), the overall median daily PM 10 flux was 1.81 g m −2 d −1 , which was slightly higher but within range of those recently published for beef cattle feedlots (McGinn et al, 2010; Bonifacio et al, 2012). McGinn et al (2010) reported values of 1.45 and 1.61 g m −2 d −1 for Australian feedlots based on inverse dispersion modeling with WindTrax. Bonifacio et al (2012) reported median PM 10 emissions of 1.10 and 1.60 g m −2 d −1 for Kansas feedlots based on a reverse dispersion modeling technique with AERMOD.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…A widely used approach involves measuring upwind and downwind concentrations combined with reverse modeling with atmospheric dispersion models McGinn et al, 2010;National Research Council, 2003;Wanjura et al, 2004). Currently, several dispersion models are available, with the American Meteorological Society/Environmental Protection Agency Regulatory Model (AERMOD) as the latest Gaussian model recommended by the U.S. Environmental Protection Agency (EPA) for regulatory purposes (CFR, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several PM emission estimates for cattle feedlots are available from studies using dispersion models, including simple box models (e.g., SJVAPCD, 2006), Gaussian dispersion models (e.g., Wanjura et al, 2004), and Lagrangian stochastic models (e.g., McGinn et al, 2010). For inventory purposes, U.S. EPA is currently using a PM 10 emission factor of 17 tons/1000 head (hd) throughput (Midwest Research Institute, 1988)(equivalent to 82 kg/1000 hd-day at 2 throughput/yr); this factor was apparently obtained using a simple Gaussian model and PM measurements from California feedlots (Grelinger and Lapp, 1996;U.S.…”
Section: Introductionmentioning
confidence: 99%